A patient decision aid for prescribing pain medication: Results from a pilot test in two emergency departments. Issue 6 (June 2021) - Omaki, Elise; Castillo, Renan; McDonald, Eileen; Eden, Karen; Davis, Stephen; Frattaroli, Shannon; Rothman, Richard; Shields, Wendy; Gielen, Andrea; ,
Highlights: An e-Health, patient education and decision aid tool was developed. The tool provides tailored education about opioids using a patient-centered approach. The tool is feasible to implement in busy emergency department settings. Acute pain patients who used the tool felt less decisional conflict about their pain treatment options. Abstract: Objective: This study piloted a patient education and decision aid tool about prescription pain relievers to determine potential impact on: comfort receiving an opioid prescription; knowledge about opioids; decisional conflict about whether to take an opioid; and shared decision making with the prescribing physician. Methods: Patients with acute pain were recruited from two emergency departments (ED), and randomized to complete the tool (N = 65) or a time-matched control (N = 59) on a tablet. Data collection involved: a baseline survey; a post-test immediately following the assigned program; a discharge survey after seeing the physician; and a 6-week follow-up survey. Results: Knowledge increased and comfort receiving an opioid decreased as hypothesized, but did not reach statistical significance. Despite the lack of knowledge differences, the tool had significant positive impact on patients feeling more informed and experiencing less decisional conflict. Shared decision making with the prescribing physician was not impacted. Conclusion: A patient decision aid can help ED patients feel more informed and less conflicted about prescription pain relievers but did not impact shared decision-making. Practice Implications: Patient education programs implemented in the ED should consider engaging physicians in the program to help to promote patient-centered approaches in the treatment of acute pain.